THEORETICAL FOUNDATIONS FOR THE DEVELOPMENT OF INNOVATIVE INFRASTRUCTURE IN THE SYSTEM OF HIGHER EDUCATION - Khamraeva Nasimovna, Sayyora; Mardonova Mamatkul kizi, Guzal (THE INNOVATION ECONOMY, 2025)
currently, more and more attention is paid to innovations and knowledge as the main force of economic growth. From this point of view, higher education is engaged not only in the training of qualified personnel, but also in the generation of new knowledge. The innovative infrastructure of higher education includes a set of institutions,resources and mechanisms that ensure the interaction of science, education and production. The purpose of the article is to study the scientific and theoretical foundations for the development of the innovative infrastructure of higher education and the scientific justification of the objective need for its development.